PERAMALAN TINGKAT PENGHUNIAN KAMAR DENGAN MEMANFAATKAN DATA GOOGLE TRENDS DI PROVINSI BANTEN - Muhammad Fajar; Teuku M. Madinah; Hendro Prayitno (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2021)
The purpose of this paper is to forecast the room occupancy rate (ROR) of star hotels by utilizing Google Trends data, in addition to historical ROR data. The data used is the ROR (%) which comes from the Badan Pusat Statistik-Statistics Indonesia and the Google Trends query index using the search word "hotel". The method used is the ARIMAX model. The results of this study indicate that the ARIMAX model has excellent forecasting capabilities. This is shown by the MAPE value which reached 6.541%, which means the added value of the hotel sector in the first quarter of 2021 is not expected to increase significantly.